Transient aerodynamic performance of high-speed trains when passing through two windproof facilities under crosswinds: A comparative study. (1st June 2019) - Yang, Weichao; Deng, E.; Lei, Mingfeng; Zhu, Zhihui; Zhang, Pingping
Highlights: A 3D unsteady incompressible numerical method is adopted. The transient characteristics of aerodynamic loads of the HST are analyzed. The sudden change mechanisms of the aerodynamic loads are revealed from flow field. Abstract: Windbreak (WB) and anti-wind open-cut tunnel (AOT) are two common windproof facilities for high-speed railways in windy areas. This study aims to determine which of them has better aerodynamic performance. For this purpose, the transient aerodynamic loads of high-speed trains are compared when passing through two windproof facilities under the same conditions of train and crosswind speeds via CFD simulation. The sudden change mechanism of aerodynamic loads and the differences in aerodynamic loads between the AOT and WB cases are revealed from the perspectives of flow field and pressure. Four main conclusions are obtained. Firstly, the fluctuation amplitudes of the five aerodynamic loads of each carriage in two periods (entry and exit) are remarkably greater than those in other periods (completely running in crosswind or windproof facilities). Secondly, the maximum fluctuation amplitudes of the five aerodynamic loads of the head carriage are generally greater than those of the rear and middle carriages during the period of entry (or exit). Thirdly, the maximum fluctuation amplitudes of side force, lift force, rolling moment, yawing moment and pitching moment of the head carriage in the WB case are 1.42, 0.84, 1.42, 1.45 and 1.44 times for the period of entry and 1.2, 1.24, 1.2, 1.58 and 2 times for the period of exit, respectively, compared with those in the AOT case. Fourthly, the maximum change rates at a time interval of 0.035 s of the side force, lift force, rolling moment, yawing moment and pitching moment of the head carriage in the WB case are 1.32, 1.26, 1.32, 1.57 and 1.52 times for the period of entry and 1.13, 1.24, 1.13, 1.42 and 1.69 times for the period of exit, respectively, compared with those in the AOT case.